Large Animal Models for Anterior Cruciate Ligament Research - Bascuñán, Ana Luisa; Biedrzycki, Adam; Banks, Scott A.; Lewis, Daniel D.; Kim, Stanley E. (Frontiers in Veterinary Science, 2019)
Large animal (non-rodent mammal) models are commonly used in ACL research, but no species is currently considered the gold standard. Important considerations when selecting a large animal model include anatomical differences, the natural course of ACL pathology in that species, and biomechanical differences between humans and the chosen model. This article summarizes recent reports related to anatomy, pathology, and biomechanics of the ACL for large animal species (dog, goat, sheep, pig, and rabbit) commonly used in ACL research. Each species has unique features and benefits as well as potential drawbacks, which are highlighted in this review. This information may be useful in the selection process when designing future studies.